2023
DOI: 10.1111/1348-0421.13045
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA MALAT1 inhibition attenuates sepsis‐induced acute lung injury through modulating the miR‐129‐5p/PAX6/ZEB2 axis

Abstract: This research aimed to investigate the role of the long noncoding RNA metastasisassociated lung adenocarcinoma transcript 1 (MALAT1)/microRNA-129-5p (miR-129-5p)/paired box gene 6 (PAX6) axis in sepsis-induced acute lung injury (ALI). MLE-12 cells and C57BL/6 mice were induced by LPS to establish lung injury in in vitro and in vivo models. Cell viability and apoptosis were measured by cell counting kit-8 assay and TUNEL (terminal deoxynucleotidyl transferase dUTP nick end labeling) staining, respectively. Leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
0
6
1
Order By: Relevance
“…Moreover, the role of miR-129-5p in LPS-induced AECII damage was also investigated. Different from the previous studies,41 miR-129-5p was revealed to protect lung endothelial or epithelial cells from LPS-induced injury by not only reducing the inflammation and apoptosis, but also alleviating the EG damage. Transfection of miR-129-5p mimics partially eliminated the damage of KCNQ1OT1 on LPS-induced AECIIs.…”
contrasting
confidence: 88%
See 2 more Smart Citations
“…Moreover, the role of miR-129-5p in LPS-induced AECII damage was also investigated. Different from the previous studies,41 miR-129-5p was revealed to protect lung endothelial or epithelial cells from LPS-induced injury by not only reducing the inflammation and apoptosis, but also alleviating the EG damage. Transfection of miR-129-5p mimics partially eliminated the damage of KCNQ1OT1 on LPS-induced AECIIs.…”
contrasting
confidence: 88%
“…MiR‐129‐5p is reported to be involved in the acute lung injury 24,41 . Thus, we hypothesized that miR‐129‐5p was required in KCNQ1OT1‐meidated AECII injury.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…LncRNA is commonly researched in human disorders, such as diseases of the respiratory system. LncRNA CASC2 is down‐regulated, lncRNA MALAT1 is up‐regulated, and lncRNA MIR3142HG is overexpressed in patients with ALI, indicating that their expression may be influenced by the occurrence of ALI 18–20 . The content of UCA1 is elevated and related to the disease severity and prognosis in patients with sepsis, which may become the cause of ALI 21 .…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs participate in various mechanisms involved in gene expression at multiple levels by interacting with RNA-binding proteins [ 16 ], DNA, and other RNA molecules [ 17 , 18 ]. In sepsis, lncRNAs regulate inflammation by acting as molecular scaffolds or decoys [ 19 , 20 ], influencing the expression of genes involved in inflammation [ 21 , 22 ], and modulating immune cell function and macrophage polarization [ 23 , 24 ]. LncRNAs can have both enhancing and suppressing effects on immune functions during sepsis [ 25 ], affecting the balance between pro-inflammatory and anti-inflammatory responses [ 26 , 27 , 28 ] and ultimately influencing the development of sepsis-associated organ dysfunction [ 22 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%